The future problem solving program international: an intervention to promote creative skills in portuguese adolescents - Azevedo, Ivete (2019)
The Future Problem Solving Program International (FPSPI) is an internationally applied educational program that involves young people. Its theoretical foundation is both the Creative Problem Solving Model and the Futurist Thinking. It aims to promote creative and critical thinking through a futurist approach to problems. This study intended to analyze the effects of the program on creative skills evaluated by the Torrance Tests of Creative Thinking (Figural Version). The participants’ perceptions of the efficacy of the program were also assessed. This intervention was carried out with 131 adolescents over a period of 7 months in an extra-curricular context. The evaluation of the program takes into account periods both before and after interventions, using similar experimental and control groups. The results showed significant statistical differences for the all skills studied and very positive perceptions of the efficacy of FPSPI. Two significant gender differences in creative performance were also found. The results are described and discussed in order to promote awareness for future research concerning this program